Makna Komunikasi Interpersonal dalam Film Keluarga Cemara - Donny Ibrahim Alsa; Ikeu Junita Triwardhani (UNISBA Press, 2022)
Abstract. Films are a form of mass media that not only provide entertainment functions, but can also provide educational and information functions for the audience. This study uses a qualitative research method with a semiotic approach. The object of this research is the film